1990
DOI: 10.1007/bf02411393
|View full text |Cite
|
Sign up to set email alerts
|

Differing substomatal and chloroplastic CO2 concentrations in water-stressed wheat

Abstract: Gas exchanges of wheat (Triticum aestivum L. cv. Courtot) shoots were measured before and during a water stress. While photosynthesis, transpiration and dark respiration decreased because of the stress, photorespiration increased initially, up to a maximum of 50% above its initial value. The CO2 concentration in the intercellular space was calculated from gas-diffusion resistances, and remained approximately constant before and during the stress. On the other hand, the CO2 concentration in the chloroplast, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
59
0
5

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 30 publications
2
59
0
5
Order By: Relevance
“…In the absence of water stress, the c c /c a ratio was around 0. 35-0.45 (Renou et al, 1990;Tourneux and Peltier, 1994). Similar results have been obtained by Ridolfi and Dreyer (1995) (1996) showed that a calcium deficiency in oak leaves induced a parallel decrease of A and c c .…”
supporting
confidence: 70%
See 2 more Smart Citations
“…In the absence of water stress, the c c /c a ratio was around 0. 35-0.45 (Renou et al, 1990;Tourneux and Peltier, 1994). Similar results have been obtained by Ridolfi and Dreyer (1995) (1996) showed that a calcium deficiency in oak leaves induced a parallel decrease of A and c c .…”
supporting
confidence: 70%
“…Moreover, it has been hypothesized that a high mesophyll resistance may be a discriminating factor between highly productive crops (with low resistances) and less productive species (as, for instance, tree species). It has also been observed that the concentration of CO 2 in the chloroplasts (c c ) decreased during drought stress (Renou et al, 1990;Cornic and Briantais, 1991;Tourneux and Peltier, 1994 where A 1% = net CO 2 assimilation under nonphotorespiratory conditions; R d = nonphotorespiratory respiration; and PFD = incident photosynthetic photon flux density (Genty et al, 1989;Epron et al, 1994;Valentini et al, 1995).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent developments, based on the use of chlorophyll a fluorescence signals to monitor light-dri\en electron fluxes (Genty, Briantais & Baker, 1989), yielded a useful tool to quantify carboxylation and photorespiration rates in situ (Peterson, 1989;Di Marco et al, 1990;Cornic & Briantais, 1991, Valentini et aL, 1995 and to compute COj availability in the chloroplasts (Roupsard, Gross & Dreyer, 1996). Thus a drought-induced decrease in chloroplastic CO, concentration (C(,) was recently reported with apparently constant CO.2 mole fractions in the substomatal spaces (c,) (Renou et al, 1990;Tourneux & Peltier, 1994;Roupsard et al, 1996). These techniques, together with on-line measurements of carhon isotope discrimination in gas exchange systems (Evans et al, 1986;Lloyd et al, 1992) also underlined that CO.â vailabihty in the chloroplasts of well watered plants was much lower than that computed for the substomata!…”
Section: Introductionmentioning
confidence: 99%
“…Ezek a mechanizmusok a többletenergiának egy biztonságos módon történő disszipációját teszik lehetővé (Osmond & Grace, 1995). A fotorespiráció (glikolát-ciklus) (Cornic et al, 1989;Renou et al, 1990;Tourneux & Peltier, 1995;Flexas & Medrano, 2002), mely folyamat a C 3 típusú növényekre jellemző, a fotoszintézis egy lehetséges alternatív útjaként jelentős lineáris elektrontranszportot képes fenntartani, így nagymértékben biztosíthatja a többlet gerjesztési energia elvezetését. Az oxigén egyes fotokémiai rendszer (PSI) általi fotoredukciója (Mehler-reakció, Asada, 1999) úgy tűnik, csak elenyésző mértékben járul hozzá az energia-disszipáció folyamatához.…”
Section: áBra a Psii Főbb Alkotórészei A D1/d2 Reakciócentrum Proteiunclassified